Self-Care Guru BK: Pelatihan Teknik Butterfly Hug pada Guru BK di Kabupaten Katingan: Self-Care for Guidance and Counseling Teachers: Butterfly Hug Technique Training for Guidance dan Counseling Teacher in Katingan Regency - Nonsihai, Nonsihai; Sendayu, Fendahapsari Singgih; Romiaty, Romiaty; Feronika, Nopi; Pasaribu, Aisha Bona Venia; Lanira, Najwa Putri; Putra, May Camaro; Mulyanto, Sri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Guidance and Counseling (BK) teachers play a crucial role in helping students navigate various issues, including personal, social, academic, and career-related concerns. However, in practice, they often face significant psychological pressures such as administrative burdens, diverse student problems, and limited support within the work environment. Therefore, practicing self-care is crucial for maintaining mental, physical, and emotional well-being, thereby preventing stress and burnout. Through self-care, BK teachers can become more balanced, resilient, and effective in providing counseling services to students. To strengthen their self-care skills, BK teachers need to be equipped with specific techniques, one of which is the butterfly hug technique. This training applied the Participatory Action Research (PAR) model, a research approach that focuses on identifying problems while simultaneously implementing practical solutions based on the findings. The program, attended by 20 BK teachers in Katingan Regency, Central Kalimantan, proved effective in enhancing their self-care abilities, both for personal well-being and in application to their students.